The Role of Typography in Loki Serial Title - Louis Cahyo Kumolo Buntaran; Agnes Indah Suciani Kristanti; Alfons Christian Hardjana (Gelar : Jurnal Seni Budaya, 2022)
This research discusses the use of typography in the title of the Loki series. As a title design, the Loki series received unfavorable comments, especially on its aesthetics. The purpose of this study was to find out how typographic elements are applied in the title of the Loki series. This type of research is qualitative using content analysis methods. It is known that the title of Loki series puts forward functions in the typographic design. So that the design is able to represent the content of the message in the story.